Resilience in the age of COVID-19. (May 2021) - Kaye-Kauderer, Halley; Feingold, Jordyn H.; Feder, Adriana; Southwick, Steven; Charney, Dennis
SUMMARY: Resilience is broadly defined as the ability to bounce back from adversity or trauma. Recent advances in resilience research have shifted away from merely describing individual characteristics towards focusing on the complex interactions between individuals and their dynamic personal, community and cultural contexts. It is clear that resilience involves both neurobiological and cultural processes. Neurobiological contributions include genes, epigenetics, stress-response systems, the immune system and neural circuitry. Culture helps to elucidate collective systems of belief and accepted positive adaptations. Importantly, resilience can also be affected by evidence-based interventions and deliberate practice on the part of the individual. This review seeks to understand resilience as a complex and active process that is shaped by neurobiological profiles, developmental experiences, cultural and temporal contexts, and practical training. It uses the COVID-19 pandemic as a case example to better understand individual and group responses to tragedy. We suggest practical recommendations to help populations around the world cope and recover from the global threat of COVID-19.